2009
DOI: 10.1021/ie8019517
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase, Microdispersion Reactor for the Continuous Production of Methane Gas Hydrate

Abstract: A continuous-jet hydrate reactor originally developed to generate a CO2 hydrate stream has been modified to continuously produce CH4 hydrate. The reactor has been tested in the Seafloor Process Simulator (SPS), a 72-L pressure vessel available at Oak Ridge National Laboratory. During experiments, the reactor was submerged in water inside the SPS and received water from the surrounding through a submersible pump and CH4 externally through a gas booster pump. Thermodynamic conditions in the hydrate stability reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to the paper reported by Taboada-Serrano et al, the experimental uncertainties were analyzed. 42 In the experiment, the error margins of the CO 2 gas hydrate formation rate γ CO 2 were about 0.7% and came from the accuracies of the temperature sensors, pressure transducers, and volumetric flow transducers, which were 0.1, 0.1, and 0.15%, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the paper reported by Taboada-Serrano et al, the experimental uncertainties were analyzed. 42 In the experiment, the error margins of the CO 2 gas hydrate formation rate γ CO 2 were about 0.7% and came from the accuracies of the temperature sensors, pressure transducers, and volumetric flow transducers, which were 0.1, 0.1, and 0.15%, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It was shown that the Higee factor β could affect the CO 2 gas hydrate formation rate and the mechanism functions supplied by the VIR could promote the CO 2 gas hydrate formation under the experimental conditions. According to the paper reported by Taboada-Serrano et al, the experimental uncertainties were analyzed . In the experiment, the error margins of the CO 2 gas hydrate formation rate γ CO 2 were about 0.7% and came from the accuracies of the temperature sensors, pressure transducers, and volumetric flow transducers, which were 0.1, 0.1, and 0.15%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A continuous-jet hydrate reactor (CJHR) developed at the Oak Ridge National Laboratory (ORNL) is another example of a multifunctional reactor (37)(38)(39)(40)(41)(42)(43). The CJHR combines a co-flow injector/reactor to convert carbon dioxide (gas or liquid) or methane (gas) and water into gas hydrates (Figure 2).…”
Section: Intensified Methodsmentioning
confidence: 99%
“…This tool can accurately measure parameters such as the fluid volume, sound wave characteristics, resistance characteristics, temperature, pressure, shear strength, and permeability . The Oak Ridge National Laboratory (ORNL) established the Seafloor Process Simulator (SPS) with a volume of 72 L to investigate the formation and decomposition processes of gas hydrates, which includes several measuring units such as digital cameras, thermocouples, pressure transducers, and gas flow meters. In Germany, the natural gas hydrate research program SUGAR established a large-scale natural gas hydrate extraction simulator (LARS, 425L), which can perform in situ catalytic combustion thermal stimulation of hydrate extraction and CO 2 replacement. It can measure the temperature, resistivity, gas-phase composition, and other parameters .…”
Section: Introductionmentioning
confidence: 99%